Bi-directional alkyne tandem isomerization via Pd(0)/carboxylic acid joint catalysis: expedient access to 1, 3-dienes. Issue 99 (28th November 2018) - Cera, Gianpiero; Lanzi, Matteo; Bigi, Franca; Maggi, Raimondo; Malacria, Max; Maestri, Giovanni
Abstract : Palladium-hydride catalysis enables dual alkyne isomerisation to conjugated dienes through an operationally simple yet mechanistically challenging route. Abstract : An in situ formed palladium hydride catalyst enables the sequential dual isomerization of propargylamide derivatives to 1-amido-1, 3-dienes with high chemo- and regioselectivity. The reaction shows ample functional group tolerance, delivering a valuable class of products, including highly deuterated ones, from readily available reagents. The reaction occurs through a complex mechanism studied by DFT modelling.